Glycobiology: an untapped source of novel drugs - Magnani, John (Henry Stewart Talks, 2012)
Glycobiology as an untapped source of innovative drugs, Rationally designed selectin antagonists based on functional carbohydrates, Application to inflammation in sickle cell disease crisis, Drug-like properties now in Phase II clinical trials, Recognition and validation of glycomimetic drugs by the pharmaceutical industry